Side Effects of Antipsychotics on Schizophrenia Patient : A Literature Review - Wilianto, Yufita Ratnasari (Pharmaceutical Journal of Indonesia, 2019)
Schizophrenia is a chronic mental disorder that is charactherized by distracted mind, behavioral changes, including delusions and hallucinations. The Â incidence of schizophrenia is 1.25% of the 2.47% of the population with psychotic disorders. Pharmacological therapy given to schizophrenia patient is an antipsychotics that works on the brain neurotransmitters including dopamine, serotonin, and glutamate. Atypical antipsychotics agents are first-line therapy for schizophrenia, whereas typical antipsychotics are used as second line when there is no improvement. However antipsychotics agents have frequent risk of side effects such as weight gain and extrapyramidal symptoms. Other reported side effects include increased prolactin levels (sexual dysfunction and menstrual irregularity), cardiovascular system (hypotension and prolonged QT interval), and lipid changes (elevated triglyceride and cholesterol). Consequences of these side effect can lead to poor adherence of patient, disease progressiveness and increase of physical morbidity and mortality. The purpose of this article is to provide a concise review of schizophrenia and discusses the side effects of atypical and typically Â antipsychotics based in literature review.